2016
DOI: 10.1016/j.biortech.2015.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic parameters of red pepper waste as biomass to solid biofuel

Abstract: This work aimed to study the kinetic of thermal degradation of red pepper waste as solid biofuel to bioenergy production. The thermal degradation experiments were conducted at three heating rates, 5°C/min, 7.5°C/min and 10°C/min in a thermogravimetric analyzer and oxidative atmosphere. The kinetic analysis was carried out applying the isoconversional model of Ozawa-Flynn-Wall. The activation energy was considerate low and varied 29.49-147.25k J/mol. The enthalpies revealed the energy difference between the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(81 citation statements)
references
References 30 publications
3
76
0
2
Order By: Relevance
“…They estimated the average E a for cellulose, hemicellulose, and lignin to be 141, 126, and 167 kJ/mol, respectively. According to their study, the E a required was the highest for lignin, which was in contradiction to the study conducted by Huang et al There are other studies available in the literature regarding the estimation of E a for different kinds of biomass using the model‐free method …”
Section: Introductionmentioning
confidence: 60%
“…They estimated the average E a for cellulose, hemicellulose, and lignin to be 141, 126, and 167 kJ/mol, respectively. According to their study, the E a required was the highest for lignin, which was in contradiction to the study conducted by Huang et al There are other studies available in the literature regarding the estimation of E a for different kinds of biomass using the model‐free method …”
Section: Introductionmentioning
confidence: 60%
“…The extent of overall combustion performance and combustion potential can be reflected by S and D b , respectively. The four pyrolysis performance indicators are as follows [22,23]:…”
Section: Pyrolysis Performance Indicesmentioning
confidence: 99%
“…The positive Δ H values suggests that higher enthalpy values indicated a less reactive system . Δ S was negative in the temperature range, which indicated that cellulose has a high degree of arrangement and physical and/or chemical processes and the disorder degree formed via bond dissociations was lower the initial reactants . The raw material has the highest enthalpy value and lowest entropy value, which indicates that its order is the largest.…”
Section: Resultsmentioning
confidence: 81%